Morfometri Ovarium Mencit (Mus musculus L. Swiss Webster) yang Terpapar Ekstrak Brotowali (Tinospora crispa L.) - Husen, Saddam - (STKIP PGRI Sumbar, 2014)
Brotowali is a traditional medicine plants, have potential be contraception. The plant have barberin, kolumbin, glukosid, pikokarotin and active substance at brotowali is alkaloid, have antiproliferative in reproduction cells. Oosit in ovarium is active cell proliferative. This aimed is research to find out morfometri ovarium of mice a treatment brotowali extract. This research is experiment research used completely randomized design, with 4 treatments and 6 replications. The treatments given was various dosage of brotowali extract, they are P1 ( given extract solvent / CMC 5 % ), (P2) a dosage of 5x10-2 mg/bb, (P3) 6x10-2 mg/bb and (P4) 7x10-2 mg/bb. This research was conducted in February 2014 in Zoology Laboratory of Biology FMIPA UNP. The parameter observed length of ovarium, wide of ovarium, sum of corpus luteum and diameter of corpus luteum. The data analisys by ANOVA. The result shows that brotowali extract not significant p < 0,05 to length of ovarium, wide of ovarium, sum of corpus luteum and diameter of corpus luteum.